AN ECONOMIC RESEARCH OF BROILER PROJECTS FOR SOME PROVINCES IN THE MIDDLE OF IRAQ IN 2019 - & Mahmood, Al-Abd alaali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This research was aimed to estimate the long-run cost and supply functions and to calculate the optimum profit-maximizing level of production, optimum capacity for broiler projects. The preliminary data were obtained by questionnaires that were distributed to project owners in Qadisiyah, Babil and Wasit governorates. A total of 80 projects amounted for 15% of the total projects in these governorates were included. The results indicated that the optimal profit-maximizing and actual production were 25,337, 34,737, and 21.25 tons respectively. The optimum production capacity was 9.9 thousand birds, while the actual capacity was 8.3 thousand chicken The cost elasticities were 0.936, 1.0 and 1.23 at the actual, optimal and profit maximizing production, respectively. The supply function had low elasticity indicating that the producers face great difficulty in controlling production in case of price changes. From these results, it can be concluded that government support is required for productive inputs, facilitating loans, preventing poultry importing, and adoption of strategic policy for the agricultural sector in general and poultry production in particular.